Design, simulation and optimization of conformal cooling channels in injection molds: a review - Silva, Hugo Miguel; Noversa, João Tiago; Fernandes, Leandro; Rodrigues, Hugo Luís; Pontes, António José (International journal of advanced manufacturing technology, 2022)
The manufacturing of conformal cooling channels (CCC’s) is now easier and more affordable, owing to the recent developments in the field of additive manufacturing. The use of CCC’s allows better cooling performances than the conventional (straight-drilled) channels, in the injection molding process. The main reason is that CCC’s can follow the pathways of the molded geometry, while the conventional channels, manufactured by traditional machining techniques, are not able to do so. Some of the parameters that can be significantly improved by the use of CCC are cooling time, total injection time, uniform temperature distribution, thermal stress, warpage thickness. However, the design process for CCC is more complex than for conventional channels. Computer-aided engineering (CAE) simulations are important for achieving effective and affordable design. This review article focuses the main aspects related to the use of CCC’s in injection molding, as follows: Sect. 1 presents an introduction, which focuses on the most important facts about the topic of this paper. Section 2 presents a comparison between straight cooling channels and conformal cooling channels. In Sect. 3 , the theoretical background of injection molding is presented. In Sects. 3 to 7 , the manufacturing, design, simulation and optimization of CCC’s are presented, respectively. Section 7 is about coupled approaches, in which several systems, methods or techniques are used together for better efficiency.